2015
DOI: 10.1007/s10984-015-9172-7
|View full text |Cite
|
Sign up to set email alerts
|

Architecture students’ perceptions of their learning environment and their academic performance

Abstract: Scholars have agreed that the way in which students perceive their learning environments influences their academic performance. Empirical studies that focus on architecture students, however, have been very scarce. This is the gap that an attempt is filled in this study. A questionnaire survey of 273 students in a school of architecture in Nigeria provided data for this pilot study. The perceptions of the students were best defined by the involvement of the students in their studies, the perceived support, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 9 publications
2
18
0
2
Order By: Relevance
“…In a study conducted by Oluwatayo et al (2015), they found that the perception of schedule inflexibility, positive assessment and equal treatment affect the overall grade of the architecture students. The researcher Demirbaş (2001) stated that through their observation, students of architecture that have a positive perception of their learning and learning environment will tend to do best in producing high-quality work.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Oluwatayo et al (2015), they found that the perception of schedule inflexibility, positive assessment and equal treatment affect the overall grade of the architecture students. The researcher Demirbaş (2001) stated that through their observation, students of architecture that have a positive perception of their learning and learning environment will tend to do best in producing high-quality work.…”
Section: Resultsmentioning
confidence: 99%
“…Malie and Akir (2012) found that hearing and explanation constitutes the learning environment preferred by most students. One study (Oluwatayo, Aderonmu, & Aduwo, 2015) investigated Nigerian architecture students' perceptions of their learning environment, and the results suggested that different aspects of the learning environment can be manipulated by educators in order to improve the performance of their students. Mapuranga, Musingafi, and Zebron (2015) found that university students in Zimbabwe thought that university support services and funding were some of the most important determinants of their performance.…”
Section: Research On the Learning Environmentmentioning
confidence: 99%
“…Within architecture, the environment of the studio has been studied by faculty researchers and noted as important to student learning (Oluwatayo et al . ). These researchers found that students’ perceptions about the studio environment were vital to their learning and concluded that studios should be positive tools of the learning process instead of negative forces.…”
Section: Introductionmentioning
confidence: 97%
“…Although the term 'desktop' is now more widely recognised as computerrelated, it aptly describes the process of standing by a student's desktop in a design studio and assessing the student's work. Within architecture, the environment of the studio has been studied by faculty researchers and noted as important to student learning (Oluwatayo et al 2015). These researchers found that students' perceptions about the studio environment were vital to their learning and concluded that studios should be positive tools of the learning process instead of negative forces.…”
Section: Introductionmentioning
confidence: 99%